Bibliometrics Analysis of Typical SCI Journals in Natural Medicines by Use of WoS. Issue 2 (3rd April 2017) - Ding, Zuoqi
ABSTRACT: On the basis of bibliometric analysis of eight typical Science Citation Index (SCI)-indexed journals in natural medicines by use of Web of Science (WoS), this study aims to find some strategies useful for improving the international impact of academic journals. We suggest that it is important to: attract foreign and internationally collaborated contributions; select reviewers and authors in citing journals of high IF; establish multidirectional collaboration with institutions that frequently publish/cite literatures and those with priority disciplines; dynamically and intensively track and analyze the terms of hot publications; and redesign the website and adopt advance digital publication.